2018
DOI: 10.1002/dvg.23098
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of Lhx3GFP reporter knockin and Lhx3loxP conditional knockout mice

Abstract: LHX3, a LIM-homeodomain transcription factor, is broadly expressed in the developing pituitary, spinal cord, medulla, retina and inner ear, and plays essential roles during embryonic development. Mice with homozygous Lhx3 null mutation exhibit failure in the formation of pituitary gland and die perinatally. To facilitate the functional study of Lhx3 in mice, we engineered and characterized two novel Lhx3 mouse strains: Lhx3 reporter knock-in and Lhx3 conditional knockout mice. Coimmunolabeling of LHX3 and GFP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…TFs are known drivers of tissue development and identity maintenance ( Uhlen et al, 2015 ). We observed high enrichment of the LHX family motif in the retina, which plays an important role in pituitary hormone deficiency associated with ocular defects ( Pérez et al, 2012 ; Xu et al, 2018 ). The second mechanism is the direct regulation of adjacent tissue-specific functional genes.…”
Section: Discussionmentioning
confidence: 88%
“…TFs are known drivers of tissue development and identity maintenance ( Uhlen et al, 2015 ). We observed high enrichment of the LHX family motif in the retina, which plays an important role in pituitary hormone deficiency associated with ocular defects ( Pérez et al, 2012 ; Xu et al, 2018 ). The second mechanism is the direct regulation of adjacent tissue-specific functional genes.…”
Section: Discussionmentioning
confidence: 88%
“…First, we compared the expression of MYO6, LHX3, and SOX2 in developing inner ears of wild‐type control and homozygous Gfi1 GCE/GCE mice at E13.5‐E17.5. The expression of hair cell markers MYO6 and LHX3 started in vestibular hair cells at E13.5 and in cochlear hair cells at E15.5 (Xu, Xie, Dong, Liang, & Gan, ), and Gfi1 GCE/GCE mice had no detectable effect on the onset and maintenance of MYO6 and LHX3 expression in the hair cells (Figure a, b). Likewise, anti‐SOX2 immunolabeling showed that the homozygous GCE knock‐in did not affect SOX2 expression in the supporting cells (Figure c), indicating normal inner ear development in Gfi1 GCE/GCE homozygotes.…”
Section: Resultsmentioning
confidence: 99%
“…The function and regulation of LHX3 have been studied in mouse models. 6,20,21 LHX3 knockout mice were stillborn or died within 24 h of birth, likely because of nervous system deficits, and they lacked anterior and intermediate pituitary lobes, with 4 of the 5 hormone-secreting anterior cell types absent. 6 Reduced expression of both LHX3 messenger RNA and protein in the Rathke pouch, the location from which the anterior and intermediate lobes of the pituitary and thereby the sites of the various types of hormone-producing endocrine cells develop, resulted in severe hypoplasia of the pouch and increased apoptosis.…”
Section: Brief Reportmentioning
confidence: 99%